Analysis of language politeness among students of SMK Teknik Balung - Kevin Ferdian Agarta; Fitri Amilia; Hasan Suaedi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study is to describe the language politeness of students at SMK Teknik Balung. The utterances taken are during teaching and learning activities and outside teaching and learning activities. This research uses qualitative method. The data and data sources are the speech of students in Balung technical vocational school which includes the maxims of wisdom, generosity, respect, simplicity, agreement and sympathy. The data collection techniques used are observation and documentation techniques in the form of free listening techniques, note taking, and recording techniques. Observation is done to find out whether the data source used is appropriate. Listening and recording techniques are used when collecting data. The recording technique was used to record the data. The data analysis is the intralingual pairing method with the comparative difference relation (HBB). The results of this study found the existence of the maxims of wisdom, generosity, respect, simplicity, agreement and sympathy. The data reflects that the students of SMK Teknik Balung have polite and well-mannered speech. The assumption given by others that students in SMK are not polite is wrong. The suggestions that can be given to future researchers are. Future researchers are expected to explain the factors that cause people to assume that students who have ethics are usually only high school students. Whereas vocational students also use polite language.